Defining end user requirements for a field-based molecular detection system for wildlife forensic investigations. (August 2019) - Masters, Alice; Ogden, Rob; Wetton, Jon H.; Dawnay, Nick
Highlights: Identification of end-user requirements for field-based DNA testing in wildlife crime applications. Instrument and assay performance defined and key species identified for priority testing. Issues to implementation and problems with current technologies explored. Abstract: The increasing use of non-laboratory-based DNA and protein detection methods promise to provide rapid investigative intelligence and support sample prioritisation. Primarily developed for human forensic or medical applications, current systems may also show utility in the field of wildlife forensic science. However, it is currently unknown whether the requirements of the wildlife forensic community can be met by current non-laboratory based tools. Given the diverse array of stakeholders and sample types commonly encountered, it is necessary to first identify the needs of the community and then try and map their needs to current instrumentation. By using a market research style questionnaire, this study identified key requirements for a non-laboratory-based system following feedback from the wildlife forensic community. Data showed that there is strong support for field-based detection methods while highlighting concerns including contamination risks and reduced quality assurance associated with non-laboratory testing. Key species and applications were identified alongside hurdles to implementation and adoption. Broadly, the requirements align with many of the developmental drivers that have led to the rise of in-field portable detection instrumentation, specifically rapid detection within one hour, ease-of-use, and ≥95% accuracy. Several existing platforms exist that met some of the identified requirements but not all. With further collaboration between industry partners and the wildlife forensic community it is possible that new field-based systems can be developed and applied routinely.